Dystroglycan 1: A new candidate gene for patellar luxation in Chihuahua dogs - Pattarawadee Srinarang (2018)
© 2018 Mansour, et al. Aim: The objective of this study was to uncover new candidate genes related to patellar luxation (PL) in dogs to select for those with low susceptibility for breeding purposes. Materials and Methods: The inter simple sequence repeat (ISSR) technique was performed to construct DNA fingerprints of 61 Chihuahua dogs with PL and 30 healthy Chihuahua dogs. DNA polymorphisms were detected by comparing the sequences between the affected and unaffected dogs, using the pairwise alignments in MultAlin. Genotyping was performed using allele-specific polymerase chain reaction (AS-PCR). The association analysis of ISSR DNA fingerprints and genotypes or phenotypes was performed using the Chi-square (χ2) model and generalized linear model (GLM), respectively. Results: Two single nucleotide polymorphisms (SNPs), namely SNP1UBC811 (g.91175C>G) and SNP2UBC811 (g.92259T>C), were found in the intron of the Dystroglycan 1 (DAG1) gene, which was obtained using the PL-related marker UBC811 primer (p=0.02), and genotyped by AS-PCR. When investigated using the GLM, g.91175C>G had a significant association with PL (p=0.0424), whereas g.92259T>C did not have such an association (p=0.0959). Conclusion: DAG1 might be one of the genes related to PL in Chihuahuas and could aid the process of marker-assisted selection in genetic breeding for Chihuahua dogs without PL.